(In press) Connecting Practice and Policy: A Case Study on the Implementation of Inclusive Design for Social Rehabilitation Center in Indonesia - Harahap, Rachmita Maun (Indonesian Journal of Disability Studies, 2026)
Sentra Mulya Jaya’s (SMJ) interior redesign in East Jakarta is essential to establishing a welcoming and cosy environment for all patrons, including those with disabilities. With a focus on multi-service delivery based on family, community, and residential needs, SMJ offers Social Rehabilitation Assistance Services (ATENSI). The purpose of this study is to determine which interior features of the SMJ facility meet the needs of users and to examine the area using the inclusive design concept. A Likert scale is employed in this mixed-methods approach, but no in-depth statistical analysis is done. Direct observation, service user interviews, and documentation analysis of spatial facilities were used to gather data. The results of the study show that SMJ’s implementation of inclusive design principles still requires work. Among the problems noted are: a) a disregard for accessibility; b) a lack of knowledge about the significance of inclusive design; and c) the detrimental effects of non-inclusive design on user experience. Inadequate accessibility considerations, a lack of education regarding inclusive design, and a failure to adequately incorporate universal design principles into the current interior layout are among the issues that have been identified. In addition to supporting the accomplishment of the Sustainable Development Goals (SDGs), especially SDG 11 on inclusive, safe, resilient, and sustainable cities and communities, this study offers specific recommendations for enhancing SMJ's interior design following inclusive design principles. It is anticipated that the results will improve service quality at Sentra Mulya Jaya and advance inclusive design theory and practice.